2020
DOI: 10.1007/s40122-020-00160-w
|View full text |Cite
|
Sign up to set email alerts
|

Kampo for the Treatment of Pain in Japan: A Review

Abstract: Kampo, a branch of traditional Japanese herbal medicine, has been the backbone of Japanese medicine for more than 1500 years. The health insurance system in Japan allows patients to access both Western and Kampo medical care at the same time in the same medical institution. Kampo has been used for the treatment of not only acute but also chronic pain in Japan. In this review, we will elaborate on the short history of Kampo, its basic concepts, and use for the treatment of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The development of plant-based medicines is performed especially in Asian countries, including Indonesia (19), Malaysia (20), Thailand (10,21), India (22), Korea (23), China (24), Japan (25,26), Iran (12,13,27), Turkey (11), Saudi Arabia (28), and Israel (17). in the countries mentioned above, herbal medicines have been used in traditional treatment for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…The development of plant-based medicines is performed especially in Asian countries, including Indonesia (19), Malaysia (20), Thailand (10,21), India (22), Korea (23), China (24), Japan (25,26), Iran (12,13,27), Turkey (11), Saudi Arabia (28), and Israel (17). in the countries mentioned above, herbal medicines have been used in traditional treatment for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research shows that most herbal medicines have been used to manage pain with minimal or no side effects. [11][12][13][14][15] A previous evaluation reported that lipoic acid, curcumin phytosome and piperine are effective complementary therapy for complimenting conventional treatments to achieve better efficacy in reducing neuropathic pain. 16 A prospective clinical trial suggested that a Chinese herbal decoction (Xiaozhi decoction) effectively relieves postoperative pain and reduces analgesic medication after hemorrhoidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, only 18 species among the 227 described contain over 10 plants ( Figure 1 ). However, the numbers of plants in polyherbal mixtures in Ayurveda ( Parasuraman et al, 2014 ), Kampo ( Arai et al, 2020 ), and traditional Chinese medicine ( Xutian et al, 2014 ) are not limited to 10. On the other hand, the species “Myrphasinum”, approved as officinal medicine in Russia, includes 12 plants ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%